The Relationship Of Maternal Knowledge With Dental And Oral Health To Caries Prevention In Pollung Village, Pollung District, Humbang Hasundutan Regency In 2023 - Kino Siboro; Megasilvia Sinaga; Nova Sontry Node Siregar; Rouli Dame Fourtri; Helprida Sihite (Sean Institute, 2024)
Caries or called cavities is one of the dental and oral health problems in most of Indonesia's population. Dental caries in children, if left untreated, will result in toothache, pulp disease, abscesses, and fistulas so that it can have an impact on the general condition of children. The national prevalence of dental and oral health is 60% while for North Sumatra province for dental and oral health the prevalence is 60%. The correct way to brush teeth for the province of North Sumatra is 1.8%. People brush their teeth every day but with the time of brushing their teeth is not correct. The purpose of this study is to determine the relationship between maternal knowledge and dental and oral health to the incidence of caries in Pollung Village, Pollung District, Humbang Hasundutan Regency. This type of research is a quantitative analytical research with a crosssectional design. This research was carried out in May-June 2023, in Humbang Hasundutan Regency. The population was 41 respondents and sampling was done using the total sampling method with a sample of 41 respondents. Data collection uses a questionnaire, then processed by chi-square test ɑ= 0.05. The results of the study showed that based on mothers' knowledge about dental and oral health using p-values (0.001) and (α=0.05). Based on the results of the study, it can be concluded that knowledge related to dental and oral health is related to the occurrence of caries. From the results of the study, it is hoped that respondents will further increase their knowledge in learning and seeing information about Aries Prevention, to maintain dental health so as to minimize the incidence of dental caries.